Perencanaan Strategis Sistem Informasi Sekolah Menengah Atas Menggunakan Ward Peppard - Jordan, Jordan; Andry, Johanes Fernandes (Fakultas Teknik Universitas Hamzanwadi, 2024)
The implementation of the information system requires strategic planning in an organization so that the benefits of implementing an information system can be felt more optimally, this will be applied to high school schools in Jakarta. The problems faced by schools are quite diverse, starting with the management of school data to performance evaluations and the need for an integrated system for each division to support the organization's business processes. Strategic planning is made with targeted targets such as alignment of information systems in academic & non-academic processes and school data management, improving performance in infrastructure management, and increasing competitiveness by creating a website-based system for school promotion. Goals can be achieved by aligning the information system strategy with the organization's business strategy. To determine the information system strategy, the organization's current business strategy is needed. This information system strategic planning research was conducted using the Ward Peppard method. This method helps to be able to understand the organization more deeply before strategic planning is made. It includes SWOT analysis, Value Chain, PEST, Critical Success Factor, and Mcfarlan's Strategic Grid analysis in the form of strategy recommendations from the results of internal and external environmental analysis of school information systems, and application portfolios will be mapped to be applied to school organizations to achieve expected business goals